Social Capital and Caregiving among Grandmothers in Rural Communities - Mattyna L Stephens; Mary Alfred (Adult Education Research Conference, 2016)
The purpose of this study was to explore the experiences of ten Black primary caregiving grandmothers in rural communities within the state of Texas to understand how they learn to develop social capital to navigate inequitable systems and acquire resources for themselves and the grandchildren in their care. The application of qualitative inquiry was essential as it best supported the probing necessary to explore the phenomenon of African American grandmothers raising grandchildren.
Keywords: Kinship Care; Social Capital; African American grandmothers; primary caregivers